Hydrogen Production by Supercritical Water Gasification of Biomass with Homogeneous and Heterogeneous Catalyst. (16th June 2014) - Jin, Hui; Lu, Youjun; Guo, Liejin; Zhang, Ximin; Pei, Aixia
Abstract : Biomass gasification in supercritical water is a clean and efficient way to convert biomass to hydrogen-rich gaseous products. Appropriate catalyst can lower the reaction temperature to guarantee the technological and economic feasibility. This paper selects Ca(OH)2, Na2 CO3, K2 CO3, NaOH, KOH, LiOH, and ZnCl2 as typical homogeneous catalysts and three kinds of Raney-Ni, dolomite, and olivine as typical heterogeneous catalysts. The catalyst effects are investigated in the process of biomass gasification in supercritical water with the temperature of 400°C, pressure of 22 ∼ 24 MPa, and residence time of 20 min. The experimental results show that Raney-Ni has the best hydrogen selectivity and hydrogen yield. The mixture of NaOH with Raney-Ni was investigated in order to research the synergistic effect of different catalysts. The experimental results show that Raney-Ni and NaOH have a synergistic effect in the biomass gasification in supercritical water.